2010
DOI: 10.1175/2010mwr3213.1
|View full text |Cite
|
Sign up to set email alerts
|

Major Extratropical Cyclones of the Northwest United States: Historical Review, Climatology, and Synoptic Environment

Abstract: The northwest United States is visited frequently by strong midlatitude cyclones that can produce hurricaneforce winds and extensive damage. This article reviews these storms, beginning with a survey of the major events of the past century. A climatology of strong windstorms is presented for the area from southern Oregon to northern Washington State and is used to create synoptic composites that show the large-scale evolution associated with such storms. A recent event, the Hanukkah Eve Storm of December 2006,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
2
37
1
Order By: Relevance
“…As physics are universal, one would expect some consistency. However, we acknowledge that consensus in this matter is lacking Á for example Mass and Dotson (2010) examined a number of cases in the Pacific northwest of America using satellite imagery, Doppler radar, surface observations and high-resolution model simulations, yet could find no evidence of SJ phenomena, and indeed proposed a model of cyclone-related wind maxima that differs somewhat from ours. Notably in their model peak winds coincide with maxima in geostrophic wind speed and curvature, rather than occurring ahead of them.…”
Section: Summary and Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…As physics are universal, one would expect some consistency. However, we acknowledge that consensus in this matter is lacking Á for example Mass and Dotson (2010) examined a number of cases in the Pacific northwest of America using satellite imagery, Doppler radar, surface observations and high-resolution model simulations, yet could find no evidence of SJ phenomena, and indeed proposed a model of cyclone-related wind maxima that differs somewhat from ours. Notably in their model peak winds coincide with maxima in geostrophic wind speed and curvature, rather than occurring ahead of them.…”
Section: Summary and Discussioncontrasting
confidence: 54%
“…Finally we would remark that there is one relatively untapped resource for windstorm study over the ocean, which is satellite-based scatterometer data. Such instruments sense capillary waves on the ocean and accordingly provide instantaneous ( Â2 seconds) wind speed estimates (for examples see Mass and Dotson, 2010;Schultz and Sienkiewicz, 2013). Although there are upper limits on speed retrieval, and coverage is discontinuous, deriving windstorm climatologies from the satellite swaths, to compare with models and re-analyses, does have the potential to provide further useful insights.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Martínez-Alvarado et al (2012) found that almost a third of the 100 most intense windstorms over the North Atlantic Ocean during winter months from December 1989 to February 2009 may have had precursor conditions that led to sting jets. Although landfalling cyclones in the Pacific Northwest may have similar surface wind maxima, Mass and Dotson (2010) found no evidence that these maxima were associated with sting jets.…”
Section: Introductionmentioning
confidence: 78%
“…Such documentary sources provide important information on the intensities and spatial footprints of historical high-impact windstorms (e.g., Lamb and Frydendahl 1991;Mass and Dotson 2010). These reports are also helpful for weather reconstruction, but need to be complemented with quantitative observations.…”
Section: Documentary Weather and Loss Reconstructionmentioning
confidence: 99%